Criminal defamation and reputation as 'honour': a cross-jurisdictional perspective. Issue 1 (2nd January 2017) - Anstey, Benedict John
ABSTRACT: Should criminal defamation be abolished, worldwide? The laws and approaches in two common-law jurisdictions – England & Wales, and South Africa – highlight some issues which must be urgently addressed in answering this question. First, the concept of reputation, which is at the heart of defamation. Judges, NGOs and others continue to make a mistake, highlighted since at least the 1980s; a basic failure to analyse this concept in sufficient depth. Second, there remains a tendency, amongst those arguing for abolition, to (inaccurately) proffer freedom of expression as a 'trump card' in these arguments. Only by addressing these issues will the abolition of criminal defamation proceed at an appropriate pace, hand-in-hand with the 'democratisation' of societies. Failure to do so could not only slow the pace of abolition, but even cause increased use of criminal defamation and an inappropriate (and potentially anti-democratic) resurgence of reputation as 'honour'.